1997
DOI: 10.1037/0708-5591.38.3.191
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, the common denominator for psychological adaptation.

Abstract: Research over the last three decades has increasingly demonstrated that sleep and its various components have a direct impact on many psychological functions such as vigilance, learning, memory, mood and psychological adaptation in general. More recently, the discovery of closer links of circadian rhythms with sleep quality has lead to the development of better intervention methods for adaptation to shift work, circadian phase disruptions and mood disorders (depressions). We present an overview of some of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…However, it should be noted that the vast majority of individuals who reported taking psychoactive medication in the previous year reported that they had not consulted a psychologist. Given (i) that there are effective psychological interventions for the problems for which these medications are routinely prescribed (Chambless et al, 1996; De Koninck, 1997) and (ii) the often expressed concerns about side-effects and compliance problems with psychoactive medication, psychologists are likely to have much to offer these individuals (cf. Barlow, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that the vast majority of individuals who reported taking psychoactive medication in the previous year reported that they had not consulted a psychologist. Given (i) that there are effective psychological interventions for the problems for which these medications are routinely prescribed (Chambless et al, 1996; De Koninck, 1997) and (ii) the often expressed concerns about side-effects and compliance problems with psychoactive medication, psychologists are likely to have much to offer these individuals (cf. Barlow, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have recognized the important role of sleep in psychological functioning (De Koninck, 1997). The quantity and quality of sleep predicts cognitive performance (see Pilcher & Huffcutt, 1996; Wesensten, Belenky, & Balkin, 2006), as well as psychological and physical health (Barton, Spelten, Totterdell, Smith, & Folkard, 1995; Dolan, Adler, Thomas, & Castro, 2005; Naitoh, Kelly, & Englund, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…This is, in part, because of a lack of psychologists trained in the behavioural sleep medicine component of health psychology. In an article published in this journal in 1997, De Koninck highlighted the impact that sleep has on several aspects of psychological functioning, and indicated that researchers and practitioners in psychology should be more attentive to sleep-related issues when working with clients or research participants. De Koninck also encouraged the integration of the topic of sleep into clinical psychology curricula.…”
Section: Discussionmentioning
confidence: 99%